Enzymatic Hydrolysis of Yellowfin Tuna (Thunnus albacares) By-Products Using Protamex Protease - Huong Thi My Nguyen; Khalifa Serigne Babacar Sylla; Zo Randriamahatody; Clair Donnay-Moreno; Jacques Moreau; Luyen Thi Tran; Jean Pascal Bergé (Food Technology and Biotechnology, 2011)
Long-term proteolysis of tuna by-products (head, viscera and tail) by the wide spectrum protease Protamex has been investigated and compared. After hydrolysis, two fractions (soluble aqueous phase and insoluble sludge) were collected. Chemical compositions of each fraction and molecular mass distributions of soluble peptides were determined. Degrees of hydrolysis obtained after 12 h of hydrolysis of head, viscera and tail were 32.3, 16.8 and 22.2 %, respectively. Nitrogen recovery in the soluble fractions was 73.6 % for the head, 82.7 % for the viscera and 85.8 % for the tail. Lipid distribution indicated that the majority of lipids remained in the sludge. Such proteolysis appears useful for the production of very different fractions: one rich in peptides of medium to small molecular mass and poor in lipids, and another one containing the insoluble proteins and the majority of lipids.